The relationship between inner child behavior and anxiety responses in adolescents - Waryanti, Emy Tri; Oktaviana, Wita (Science Midwifery, 2025)
Mental health during adolescence plays a critical role in emotional and social development. One potentially influential factor is unresolved childhood emotional trauma, known as inner child behavior. This study aims to examine the relationship between inner child behavior and anxiety responses in adolescents. A correlational quantitative design was used, involving 102 students from SMA Batik 1 Surakarta selected through proportional random sampling. Inner child behavior was assessed using the standardized Wounded Inner Child Questionnaire, which contains 83 items with validity coefficients ranging from 0.196–0.765. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (SAS), which consists of 20 items with validity coefficients ranging from 0.663–0.918. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Most respondents showed moderate inner child behavior (63.7%) and mild anxiety levels (51.0%). Chi-Square analysis revealed no statistically significant relationship between inner child behavior and anxiety responses (p = 0.119). The study concludes that there is no significant correlation between inner child behavior and anxiety responses among adolescents. Future research should consider emotional expression barriers and data variability.